2014
DOI: 10.1128/aac.02641-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cryptosporidium parvum Active Chemical Series by Repurposing the Open Access Malaria Box

Abstract: The apicomplexan parasites Cryptosporidium parvum and Cryptosporidium hominis are major etiologic agents of human cryptosporidiosis. The infection is typically self-limited in immunocompetent adults, but it can cause chronic fulminant diarrhea in immunocompromised patients and malnutrition and stunting in children. Nitazoxanide, the current standard of care for cryptosporidiosis, is only partially efficacious for children and is no more effective than a placebo for AIDS patients. Unfortunately, financial obsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 41 publications
0
63
1
Order By: Relevance
“…Imidocarb exhibited IC 50 values of 230 to 690 nM against the Babesia parasite species, and we observed IC 50 (13). The breadth of babesiacidal Malaria Box inhibitors is striking in relation to the comparatively few Malaria Box inhibitors reportedly active against nonerythrocyte apicomplexans, such as T. gondii, C. parvum, and T. annulata (14)(15)(16). We speculate that this difference may reflect the existence of conserved targets required for proliferation within a similar erythrocytic niche for diverse apicomplexan hemoprotozoan parasites and/or the close phylogenetic relatedness of Plasmodium and Babesia spp.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Imidocarb exhibited IC 50 values of 230 to 690 nM against the Babesia parasite species, and we observed IC 50 (13). The breadth of babesiacidal Malaria Box inhibitors is striking in relation to the comparatively few Malaria Box inhibitors reportedly active against nonerythrocyte apicomplexans, such as T. gondii, C. parvum, and T. annulata (14)(15)(16). We speculate that this difference may reflect the existence of conserved targets required for proliferation within a similar erythrocytic niche for diverse apicomplexan hemoprotozoan parasites and/or the close phylogenetic relatedness of Plasmodium and Babesia spp.…”
mentioning
confidence: 74%
“…In 2011, the nonprofit group Medicines for Malaria Venture (MMV) made available to the research community the Malaria Box, a collection of 400 chemically diverse, previously uncharacterized blood-stage antimalarials (13). Researchers have screened the antiparasitic activities of the Malaria Box compounds in nonerythrocytic host cells for the apicomplexans T. gondii, Cryptosporidium parvum, and Theileria annulata and identified a limited number of inhibitors (Ͻ3% of the library) active against each of these species (14)(15)(16). Here, we measured the susceptibilities of multiple blood-stage Plasmodium and Babesia parasite species to the Malaria Box compounds and found that erythrocyte-specific apicomplexans share considerable chemical sensitivities during the clinically relevant stages of parasitic infection.…”
mentioning
confidence: 99%
“…In a very recent study, a strategy similar to ours was adopted to repurpose the open access Malaria Box to identify chemical series active against Cryptosporidium parvum (42). The authors showed in a subsidiary objective that the 2,4-diamino-quinazoline-based compounds were also potent growth inhibitors of the related apicomplexan parasite T. gondii of the RH strain from which the TS-4 strain used in our study was derived.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need to define new targets and to identify compounds that effectively inhibit parasite growth. An added challenge in working with Cryptosporidium is that it does not undergo continuous propagation in vitro, although short-term tissue culture assays have been used to screen for small-molecule inhibitors of C. parvum replication (9,10).…”
mentioning
confidence: 99%